Sistem Pengelolaan Arsip Unit dalam Negeri dan Kliring di PT Bank Negara Indonesia (Persero) Tbk Kantor Cabang Utama Padang - Juwita, Lasmi; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2016)
This paper discussed the archival management system of the interior and clearing unit atÂ PT. Bank Negara Indonesia (Persero) Tbk. Main branch office Padang. The purpose of this paper is (1) to describe how the records management system of the interior and clearing unit at PT. Bank Negara Indonesia (Persero) Tbk. Main branch office Padang; (2) describe any obstacles encountered in the process of records management unit of the interior and clearing in the PT. Bank Negara Indonesia (Persero) Tbk. Main branch office Padang; (3) describe the efforts made to overcome the obstacles in the process of records management unit of the Interior and clearing in the PT. Bank Negara Indonesia (Persero) Tbk. Main Padang.Data were collected through observation, interviews, and literature. interviews with the leaders of the Interior and clearing unit, unit supervisor of the interior and the clearing and general staff in PT. Bank Negara Indonesia (Persero) Tbk. Main branch office Padang. Analyzing data descriptive.Â Keyword: management; archives; domestic; Clearing Unit